Analisis Design Thinking Iklan KPU di YouTube Menjaring Pemilih Pemula Pemilu 2024 - Binasri, Binasri; Witarti, Denik Iswardani (Jurnal Pustaka Komunikasi, 2024)
The government, through the official institution responsible for elections, the General Election Commission (KPU), seeks to ensure the success of elections to be participated by all eligible citizens. The KPU has conducted socialization, one of which is to attract beginner voters, who are young, inexperienced and have limited knowledge about politics, especially elections. Through public service advertisement videos on YouTube. This study aims to examine whether this advertisement effectively reach out to beginner voters by analyzing the themes and content of the messages. The approach used is descriptive-qualitative analysis using the design thinking concept by Tim Brown. The research findings on the rationale behind this advertisement. The concept of this advertisement version " Gunakan Hak Pilihmu di TPS," with a romantic setting, demonstrates the ad creator's cleverness in linking the election date, February 14, known worldwide as Valentine's Day. This serves as an entry point in developing the advertisement idea. Election messages are conveyed through the teenage couple’s conflicts, leading to a happy ending and urging them to exercise their voting rights in 2024 election. The conclusion from this research is the theme and message content of this advertisement are appropriate and capable to attracting and capturing beginner voters.